Inventing the council inside the Apostolic Library: the organization of curial erudition in late cinquecento Rome - Malesevic, Filip (De Gruyter, 2021)
The book provides a detailed study of the Biblioteca Apostolica Vaticana and its interior decoration which today still remains inaccessible to the ordinary visit. Placing the history of the Vatican Library in the larger context of how erudition was administered and organized within the Early Modern Roman Curia, the book will also take into consideration how the Vaticana was used in contrast to other newly founded libraries